Social Interaction as a Determining Factor of Friendship Quality in the Novel Melangkah by Js Khairen. - Inayah Nuraulia Mokodongan; Sitti Rachmi Masie; Herman Didipu (Raja Zulkarnain Education Foundation, 2026)
Friendship is a fundamental social institution that serves as a forum for social interaction and psychological support for adolescents and young adults. This study examines the determinants of friendship quality in JS Khairen's novel